Transforming Classroom Practices: A Christian Worldview Perspective on Teacher Beliefs - Mendrofa, Helni Berlian; Feni, Septiana; Puspitasari, Dani (Sekolah Tinggi Teologi Bethel The Way, 2025)
Belief and faith are two interchangeable dimensions that possibly affect one’s decision. Significance literature shows that beliefs are formed by knowledge and experience. However, this study also incorporates faith as part of one’s journey in shaping a professional teacher’s belief. This study examines a Christian teacher believes in managing her classes with misbehaving students and whether the actual classroom practices follow these beliefs. A qualitative method through observation and interviews was implemented. Findings generate that a teacher's knowledge and experience are closely related to the Christian Worldview. It guides her decisions and actions. However, in some situations, the teacher could not perform her beliefs because of external factors.